Soil Remediation Environmental Decision Support System Based on AHPPROMETHEE II Approach - Xie, Tao; Hai, Reti; Quan, Xiangchun; Li, Anjie; Liu, Rui; Chen, Yaxin (Journal of Environmental Accounting and Management, 2026)
Multi-criteria analysis was used to compare technology solutions for 3 Selection of soil remediation technologies for contaminated sites is difficult given the large number of technologies available and the economic, social, and environmental impacts of site remediation activities. In this paper, we take into account a multitude of consequences and analyze their impacts with multi-criteria utility theory. By establishing the AHPPROMETHEE II (Analytic Hierarchy Process-Preference Ranking Organization Method for Enrichment Evaluations II) method, an Environmental Decision Support System (EDSS) has been developed for the purpose of identifying optimum soil remediation approaches for contaminated site. In the EDSS, AHP is used to structure the decision problem and to attribute weights to the criteria, whereas PROMETHEE is used to obtain a final ranking of the proposed alternatives. In addition, the hierarchical decision tree was constructed according to 4 criteria, i.e., time and economic costs, technical levels, technical applicability and social benefits, 12 indicators, and 21 soil remediation alternatives. The system has been applied to a case study, in which the best option of soil remediation technology for the particular remediation goal could be achieved. The effectiveness and shortcomings of this system are also discussed.